FREEDOM TO PROVIDE SERVICES, AS ONE OF THE FOUR FREEDOMS OF THE EUROPEAN UNION’S SINGLE MARKET AND ITS DEVELOPMENT IMPLICATIONS FOR BOTH MEMBER STATES AND NATIONAL ECONOMIES OUTSIDE THE EU - Jolevski, Zoran (International Scientific Journal Vision, 2022)
The service sector plays a dominant role in the national economies of the EU member-states whare over 2/3 of GDP is generated in this sector. International trade in services is different from trade in goods and therefore special measures are needed to ensure the free movement of services within the Single Market. The studies of the European Commission show that as a result of the implementation of the regulations related to the freedom of movement of services, the GNP of the EU member-states is growing and new jobs are being created. Proper implementation of this freedom also contributes to improving the competitiveness of the European economy on the world market. In order to ensure the free export of services, it is necessary to adopt a regulation that provides freedom in the incorporation (establishment of companies) in the territory of the EU мember-states in which the services are consumed, recognition of diplomas and professional certificates of service providers, as well as rules that allows free consumption and provision of services in the territory of another member-state.